Environmentally friendly, non-glove box, closed-system and continuously massive production of lithium sulfide for battery applications. (1st January 2023) - Yang, Shunjin; Wan, Fengming; Han, Aiguo; Fang, Liran; Sun, Qifang; Zhao, Zixiang; Song, Dawei; Zhang, Lianqi; Chen, Lifang; Wolden, Colin A.; Zhang, Xin; Yang, Yongan
Abstract: Lithium sulfide (Li2 S) is an important material for lithium-sulfur batteries and solid-state batteries. However, its prohibitive price hinders the practical development of these technologies, reflecting multiple problems in existing production processes including high temperature/energy demands, greenhouse gas emissions, low yield, low purity and the use of air sensitive equipment. Herein we report the development of an environmentally friendly process for the scalable production of Li2 S without need for a glove box. The net chemical process is the reaction between Li metal and hydrogen sulfide (H2 S) with ethanol as the auxiliary solvent, which can in principle be recovered and recycled. The production capability reaches 1.0 kg_Li2 S/day, 50–100 times greater than the largest scale reported in the literature. The material quality of the resulting Li2 S is validated through its use as a cathode material in lithium-sulfur batteries, achieving essentially comparable performance with commercial Li2 S. Moreover, additional value is provided by concomitant H2 production which is demonstrated through its use for the in-situ reduction of copper oxide. We believe that the process described by this work can be readily adapted to support the developments of advanced batteries. Graphical abstract: Image 1